The Kanyana food challenge: Food systems mapping - Linderhof, Vincent; Dijkxhoorn, Youri; Onyango, Joel; Fongar, Andrea; Nalweyiso, Martha (2019)
NOURICITY is a LEAP-agri funded project and its objective is to initiate and implement partnership agreements between stakeholders of the urban food system on healthier food choices. The project is explored in Accra (Ghana), Cape Town (South Africa) and Kampala (Uganda). The project is funded by the EU and national donors. For the Kampala case, the project is led by Wageningen Economic Research and executed together with Bioversity International, and BoP innovation centres. Wageningen Economic Research is funded by the Dutch Ministry of Agriculture, Nature and Food Quality. This progress report describes the results of various activities of WP1 of the NOURICITY project implemented in the year 2019.